BATTLE FOR THE COVID-19 GLOBAL NARRATIVES: The Tanzanian Online Discourse on Millard Ayo's Instagram - Basebya, Kwizela Aristide (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
Amidst COVID19, Beijing was in diplomatic tension with its ‘all-weather friend’ Africa for allegedly targeting Africans in efforts to combat imported cases. As it is in the battle for covid-19 global narrative, U.S. and China faced off. The U.S. took a “condemning China approach,” while China applied “blaming the U.S. of sowing discord on China-Africa friendship.” This study purposely and comparatively picks the two narratives with 1253 pro-U.S. and 683 pro-China total comments as posted on a Tanzanian blogger, Millard Ayo’s Instagram page of 7.2 million followers. It randomly selected 514 (41%) and 276 (40.4%) comments from the two narratives. Through tracking online discourse, coding, and analyzing dominant thematic issues, findings reveal that few netizens asserted China’s story on the incidents, with a significant number supporting retaliation against China. Although the U.S. “condemnation narrative” received high approval, the majority of comments also questioned its moral authority. Interestingly a considerable number of words branded both U.S. and China ‘imperialists’ racing for Africa’s natural resources and wealth. Overall, this research reveals the prevalence of flaws in the Sino-Africa relationship and that the reported discriminations have further worsened the ties, at least for ordinary people. To cite this article (7th APA style):Basebya, K. A. (2020). Battle for the Covid-19 Global Narratives: The Tanzanian Online Discourse on Millard Ayo's Instagram. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), 94-104. http://dx.doi.org/10.36782/jcs.v10i2.2080